Rearrangement and Degradation of 3a,7a-Dihydroindole Esters - Lee, Do-Hun (Asian Journal of Chemistry, 2015)
The purpose of this paper is to report that pyrroles 1a-c also gave the 1:2 adducts 3a-c when refluxed with dimethyl acetylene dicarboxylate in ether (or ether with AlCl3) and rearrangement and degradation of 3a,7a-dihydroindole esters 3a-c as 1:2 molar [4+2] cycloadducts were investigated. The electrons in compound 3a are assumed to move as in its resonance structure A which should results in the formation of transition state B. Next, cleavage of the C-C bond between the carbonyl carbon atom and the 3a carbon atom and the 1,3-shift of the hydrogen atom from 7a position into 2 position will occur easily to form an aromatized stable indole compound 4a.